A Non-Stop Ice-Melting Method for Icing Lines in Distribution Network Based on a Flexible Grounding Device - Yabing Zhou; Fang Yang; Jiaxin Xu; Xiaoliang Tang; Jiangyun Wang; Dayi Li (Energies)
Icing on transmission lines poses a serious threat to the power grid. Existing de-icing solutions have limitations in short-distance distribution networks with multiple branches. We propose a method that utilizes a flexible grounding device to adjust the zero-sequence reactive current in the distribution network, enabling de-icing of lines without power interruption. Simulation and experimental results validate the feasibility and effectiveness of the proposed method and control scheme. The method can accurately regulate the de-icing current to achieve de-icing under various conditions, with the actual de-icing current deviating from the set value by less than 0.3%. During de-icing, the line voltage on the load side remains essentially stable, with an error of less than 0.5%, ensuring that the normal supply voltage of the distribution network is not affected, and the entire network load does not require a power outage. The de-icing device interacts only with reactive power in the distribution network, saving capacity for the DC voltage stabilizing power supply and demonstrating good economic efficiency.